Tempe Koro Benguk (Mucuna pruriens L) dan Pengendalian Glikemi: Studi pada tikus Sprague Dawley yang Diinduksi Streptozotocin - Ch. Retnaningsih; Darmono Darmono; Budi Widianarko; Fatimah Muis (MEDIA MEDIKA INDONESIANA, 2013)
ABSTRACTVelvet bean tempe and glycemic control in streptozotocin induced Sprague Dawley ratsBackground: Modern treatment combined with functional food rich in antioxidants show the considered to control glycemic status. Such functional food is velvet bean tempe (VBT) rich in flavonoids. The study aimed to analyze the effect of the velvet bean tempe on glycemic control i.e. the blood glucose levelMethods: A randomized controlled group pre test-post test design using 50 male Sprague Dawley (SD) rats aged 2-3 months was carried out for 30 days. The rats were randomly allocated into 5 groups: negative control (C-), positive control (C+), streptozotocin (STZ)+10%VBT, STZ+20% VBT, STZ+30% VBT. Data were analyzed with paired T test, one-way Anova and continued with Duncan’s multiple range test. Analysis of blood glucose levels used with super glucocard II test meter, and for C peptide levels ELISA was used.Result: Supplementation of VBT 20% and VBT10% reduced the level of blood glucose until 46.1% and improve the level of C peptide until 44,3±8,3 pg/ml respectively.Conclusion: Velvet bean tempe has the potency as functional food to help controlling glycemic status.Keywords: Velvet bean tempe, glycemic control, streptozococinABSTRAKLatar belakang: Pengobatan modern dikombinasikan dengan pangan fungsional yang kaya antioksidan dapat menjadi pertimbangan untuk memperbaiki status glikemi. Jenis bahan pangan tersebut adalah tempe koro, memiliki banyak senyawa antioksidan flavonoid. Penelitian ini bertujuan untuk membuktikan pengaruh tempe koro benguk terhadap pengendalian status glikemi pada tikus Sprague Dawley yang diinduksi streptozotocin.Metode: Penelitian randomized pre test-post test control group design, dilakukan menggunakan 50 ekor tikus jantan jenis Sprague Dawley umur 2-3 bulan selama 30 hari yang dibagi kelompok kontrol negatif/C-; positif/ C+; STZ+ tempe koro benguk 10%; STZ+tempe koro benguk 20%; STZ+tempe koro benguk 30%. Dilakukan pemeriksaan glukosa darah menggunakan super glucocard II test meter dan C peptida menggunakan ELISA.Hasil: Asupan tempe koro benguk dalam berbagai dosis menurunkan kadar glukosa hingga 46, 1% dan penurunan terbesar pada tikus yang diberi tempe koro benguk 20%. Selain itu tempe koro benguk dapat meningkatkan kadar C peptida hingga 44,3±8,3 pg/ml, peningkatan terbesar pada tikus yang diberi tempe koro benguk 10%.Simpulan: Tempe koro benguk dapat dipertimbangkan sebagai pangan fungsional dalam mengendalikan glikemi pada tikus hiperglikemi.